Pengaruh Penambahan E-Glass Fiber Terhadap Kekuatan Kompresi Resin Komposit Nanofil - Fahrini, Nurul; , drg. Noor Hafida Widyastuti, Sp.KG; , drg. Ariyani Faizah, MDSc (2016)
Nanofill composite resin was a new composite resin with good aesthetic properties, polymerization shrinkage were small and had a high filler. Besides these advantages, the composite resin nanofill also has the disadvantage that the compressive strength was still lower than the resin composite microfill and microhybrid. The purpose of this study was to saw the effect of the addition E-glass fiber on compressive strength of resin composite nanofill.This study used a sample of the resin composite molds which were be divided into two groups: the first group of resin composite with the addition of E-glass fiber and second group was resin composite without the addition of E-glass fiber. The sample size was a diameter of 3 mm and high 6 mm by 32 pieces with each group of 16 pieces. Specimens were stored in distilled water for 24 hours and incubated at 370 C. The test compression strength used the universal testing machine with a crosshead speed of 1 mm / min. The test data were analyzed using t-test Independent test.The results showed that between the two study groups there were different compression strength values were significantly, p = 0.000 (P <0.05) so that it can be concluded that there is a difference in the compression strength of the composite resin nanofill between the use of E-glass fiber and without the addition of E- glass fiber. Compression strength of resin composite nanofill with the addition of E-glass fiber proved the results values greater than of compression strength without the addition of E-glass fiber.